The Complex Effect of Food Matrix Fat Content on Thermal Inactivation of Listeria monocytogenes: Case Study in Emulsion and Gelled Emulsion Model Systems - Verheyen, Davy; Govaert, Marlies; Seow, Ti Kian; Ruvina, Jonela; Mukherjee, Vivek; Baka, Maria; Skåra, Torstein; Van Impe, Jan F. M. (Frontiers in Microbiology, 2020)
Previous studies on the influence of food matrix fat content on thermal inactivation kinetics of food pathogens have shown contradictory results due to the combined influence of fat content and other factors such as composition. Therefore, thermal inactivation of Listeria monocytogenes at 59, 64 and 69°C was systematically investigated in emulsion and gelled emulsion food model systems with various fat content (1, 5, 10, and 20%), such that the effect of fat content was isolated. Thermal conductivity and rheological properties of the model systems were quantified, as well as the effect of these properties on the thermal load of the model systems. Thermal conductivity was complexly related to fat content, the nature of the food matrix (i.e., viscous or gelled), and temperature. For the emulsions, the consistency index K increased with increasing fat content, while the flow behavior index n followed the opposite trend. For the gelled emulsions, the storage modulus G’ was always larger than the loss modulus G” (i.e., measure of elastic and viscous properties, respectively). The phase angle δ [i.e. arctan (G”/G’)] was proportional with fat content, but this relation became more complex at higher temperatures. The thermal load of the model systems was not largely affected by food matrix fat content. Thermal inactivation of L. monocytogenes was investigated by means of the maximum specific inactivation rate kmax, log reductions, and sublethal injury (SI). Both for emulsions and gelled emulsions, kmax decreased with increasing fat content below approximately 60°C, while a more complex behavior was observed at higher temperatures. In the emulsions, log reductions were considerably lower (i.e. 2-3 log) at 1% fat than in systems with higher fat content. In the gelled emulsions, log reductions generally decreased with increasing fat content. SI decreased with increasing fat content, both in emulsions and gelled emulsions. In conclusion, the inactivation rate (i.e. kmax) of L. monocytogenes was affected by a complex relation between food matrix fat content, thermal conductivity, rheological properties, and inactivation temperature. Due to the small scale of the model systems, differences in kmax did not directly affect the final log reductions in a similar fashion.